THE FUNCTION OF SATIRE IN 18TH CENTURY BRITISH LITERATURE - Muborova Zarina (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
The 18th century in British literature was marked by profound societal and political changes, and satire played a crucial role in critiquing these shifts. This paper explores how satirical works from prominent authors such as Jonathan Swift, Alexander Pope, and John Dryden provided sharp commentary on social, political, and moral issues. The genre’s satirical function not only mocked and ridiculed the aristocracy and political figures but also reflected the broader cultural tensions of the Enlightenment period. By examining key works like Gulliver’s Travels and The Rape of the Lock, this study argues that satire in 18th-century British literature served as a tool for both social reform and intellectual discourse, ultimately shaping the future of literary satire.